Analisis Pengaruh Geometrik Dan Kelengkapan Rambu Lalu Lintas Terhadap Kecelakaan (Studi Kasus : Tanjakan Kethekan Kec. Jambu, Ruas Jalan Ambarawa – Magelang Km. 46+000 S/D 46+750) - Rizqi Rangga Perdana; Yeremia Kristian Adi Permata; Siti Latifah; Sukoyo Sukoyo; Wasino Wasino (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
Ambarawa – Magelang main road is an arterial road which used by drivers who came from Central Java headed to Yogyakarta. The Road Segment is considered to have frequent traffic accidents. The study aims to analyze the relationship between geometric aspects and the occurrence of accidents, compare actual speed with plan speed, and analyzing the completeness of the traffic signs on this section to identify the causes of accidents that occurred at that location. The stages of analysis is by doing the geometric calculation of the road and compared with the requirements in the regulation then identifying whether there is a relationship between accidents that occur with geometric conditions, vehicle speed, and the signs completeness. Identification and results of geometric analysis is known that Black Spot are on bend road I (km 46+300) there were 22 accidents due to breaking road markings, 6 accidents due to extreme bend, and 4 accidents due to road slackness throughout 2012 – 2018. On the bend road II (km 46+440) there were 5 accidents due to breaking road markings and on the bend road III (km 46+520) there were 3 accidents due to road slackness. with the result that there is a relationship between geometric conditions with accidents that occur and after being analyzed the completeness of the traffic signs is still lacking and needs to be completed.